Penerapan Kesehatan Dan Keselamatan Kerja Pada Wisata Paralayang Di Gunung Banyak, Kota Batu, Provinsi Jawa Timur - Adz Dzikri, Muhammad Alif; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i02.p10, 2019)
The aim of this study is to analyze the workplace health and safety of the employee and visitor of Paragliding Tourism at Gunung Banyak, Batu East Java. This recreation has become the new tourist attraction for both domestic and international tourists. This makes the basis of this study to identify the factors that cause the accidents may happen to the employee and visitor, as well as the prevention done to minimize it and how to handle it when actually happens. The data used is the qualitative data, while the source taken from primary and secondary data. The data collecting process are conducted through an observation, interview and literature review. The data are analyzed qualitatively. The result shows that Health and Safety procedure in Paragliding Tourism is the main thing as most of it has been applied on the field. However, some improvements are still needed in the procedure for the maximum safety of both employee and visitor. The suggestion given to the owner of the Paragliding Recreation is to continue to watch the implementation of health and safety of Paragliding Tourism. As for the visitors are also suggested to always follow the rules and the instructor’s direction. The writer hopes this study will give brief summary of the implementation of health and safety procedure at the Paragliding Toursm, and will eventually be useful for the next more detailed study. Keywords: Paragliding Tourism, workplace health and safety, Mount Banyak of Batu City.